NILAI TAMBAH KEDELAI MENJADI TAHU KUNING DAN FAKTOR-FAKTOR YANG MEMENGARUHINYA - Dinda Yunita Yosifani; Ratna Satriani; Dindy Darmawati Putri (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2021)
One of the home industries for processing soybeans into tofu is located in Kalisari Village, which has been producing since 1965. This business serves as a diversification of the business that can increase household income. This study aims to 1) determine the added value of soybeans obtained by producers, 2) determine the distribution of the added value of soybeans to yellow tofu, and 3) determine the factors that affect the added value of soybean on yellow tofu production. The research was conducted on tofu producer in the Sari Delai Group in Kalisari Village, Cilongok Sub-district, Banyumas Regency in June-July 2020. Then added value analysis is carried out by using the method of Hayami and multiple linear regression. The results showed that 1 kg of soybean raw material used for yellow tofu will provide an added value of Rp. 11,628.00. The distribution of added value for labor income was 13.38 percent, other input contributions by 18.54 percent and for profit 68%. The production capacity, raw materials, labor, output price and other input contributions have significant effect on the added value of yellow tofu production. In contrast, labor wage and raw material prices have no effect on the added value of yellow tofu production.